Analisis Persepsi Konsumen Tentang Atribut Produk ( Merek, Ciri Produk, Jaminan Dan Kualitas) Yang Dimiliki Sepeda Motor Matic Honda Vario Terhadap Keputusan Pembelian - Lestari, Eka Anggraini; Maruta, Anom; Nasution, Ute Chairuz (Jurnal Dinamika Administrasi Bisnis, 2017)
This research is a quantitative research, sampling in this study there were 100 respondents in cluster random sampling, while anlisis data used is multiple linear regression. The purpose of this study was to analyze consumer perception of product attributes (brand, product features, warranties, quality) influence on purchase decisions matic Honda Vario among students in the city of Surabaya either simultaneously and partially. Results of research conducted shows that consumer perceptions of the attributes of the product (brand, product features, warranties, quality) significant effect simultaneously on purchasing decisions, while the brand a significant negative effect on purchasing decisions, product features positive significant effect on purchasing decisions, guarantee significant effect positive on purchasing decisions, and a positive significant effect on the quality of keutusan purchase. Â Keywords: brand, product features, warranties, quality on purchasing decisions